Politik Implementasi Program Bantuan Stimulan Perumahan Swadaya (BSPS) sebagai Inovasi di Desa Jelutung II Kecamatan Simpang Rimba Tahun 2020 - Renia Renia; Bustami Rahman; Sarpin Sarpin (Jurnal Studi Inovasi, 2022)
Abstract Renia, the politics of implementing the self-help housing stimulant assistance program (BSPS) in Jelutung II village, Simpang Rimba sub-district in 2020, was guided by Bustami Rahman and Sarpin. Implementation is an activity, action and action. However, implementation is not just an ordinary activity, but the implementation of planned activities to achieve a set goal. However, the implementation of a program cannot be realized easily. There are several factors that are taken into consideration for the success of the implementation. The more these factors are ignored, the more difficult it is to achieve the objectives of the policy. The purpose of this study was to determine the politics of implementing the self-help housing stimulant assistance program (BSPS) and to analyze the supporting and inhibiting factors for the implementation of the BSPS program in Jelutung II Village. This study uses the policy implementation theory of Merilee S. Grindle as the basic foundation of the research. Regarding the concept of policy implementation, there are two major variables, namely, the first is the content of the policy which contains six other indicators, namely; the interests of the target group (target group), the types and benefits received by the target group, the degree of desired change, the location of a program, program implementation or implementers and resources. Then, based on the policy environment, there are three other indicators, namely: a) the power, interests, and strategies of the actors involved. b) characteristics of institutions and authorities c) compliance and responsiveness. The method used in this research is a descriptive qualitative method with primary data sources derived from unstructured interviews with 19 informants. The informants consisted of 2 village officials who were responsible for the service delivery division in the BSPS program in Jelutung II Village, 1 TFL BSPS Jelutung II villager, 9 recipients of the BSPS program and 9 non-recipients of the BSPS program. The results of this study indicate that the implementation of the Self-Help Housing Stimulant Assistance (BSPS) program in Jelutung II Village, Simpang Jungle District has been implemented even though it has been less effective. Based on several policy implementation factors, according to Grindle, there are some that are less effective in implementing the BSPS program policy in Jelutung II Village. This can be seen from the time of determining the prospective recipients of assistance, there are still recipients who are not appropriate as well as delays in building goods and the limitations of the existing budget from the recipients. The supporting factor of the BSPS program in Jelutung II Village is the good quality of building materials. The inhibiting factors are weather, availability of builders and delays in building materials. Keywords: Policy, Implementation, BSPS, Jelutung II village.